Religious-Cultural Mediation in Technology Adoption: A Qualitative Study of Islamic Communities in Indonesia - Ramdani, Idan; Apri Wenando, Febby; Ondri, Dino (Surau Journal of Islamic Studies, 2025)
This research aims to analyze the influence of Islamic social and cultural values on technology adoption within Muslim communities, focusing on the challenges and opportunities arising from the misalignment between technological advancements and local cultural values. Technology adoption in Muslim societies is often influenced not only by infrastructure readiness but also by societal perceptions of technology that may conflict with long-standing religious doctrines and cultural traditions. This study identifies three main factors affecting technology acceptance: infrastructure readiness, social disparities, and the cultural characteristics of Islam. The research demonstrates that successful technology adoption requires social engineering that enables integration with the existing moral and social values in Muslim communities. Using a qualitative approach, the study explores how Muslims adapt technology without compromising their religious and cultural principles. Findings indicate that effective technology adoption necessitates policies accommodating local social and cultural values and the involvement of religious leaders in introducing appropriate technology. This research significantly contributes to enriching the study of technology adoption by considering cultural and religious dimensions and opens opportunities for further research in this field. The study’s limitation lies in its geographically limited scope, suggesting the need for broader, more in-depth research involving Muslim communities in various regions.